2006
DOI: 10.1182/blood-2006-06-031856
|View full text |Cite
|
Sign up to set email alerts
|

l-arginine availability regulates T-lymphocyte cell-cycle progression

Abstract: IntroductionL-arginine (L-Arg) is a nonessential amino acid that plays a central role in regulating the immune response. 1 In mammalian cells, L-Arg can be catabolized by 4 enzymatic pathways, namely nitric oxide synthase, arginases I and II, arginine:glycine amidinotransferase, and arginine decarboxylase. L-Arg is profoundly reduced in cancer patients, 2 following liver transplantation, 3 or in severe trauma 4 by an increased production of arginase I. This results in a decreased T-cell proliferation and an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
627
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 739 publications
(667 citation statements)
references
References 30 publications
22
627
1
8
Order By: Relevance
“…These results suggest that T cells have a predesigned program to handle amino acid starvation and that when LAT1 expression is impaired, T cells turn on such a system for restraining the immune response to avoid waste of energy and resources. Interestingly, it has been shown that GCN2 also induces cell cycle arrest by suppressing cycline D3 expression in arginine-starved T cells (39). This and our results suggest that GCN2 functions as a central factor for amino acid starvation response in T cells.…”
Section: Discussionsupporting
confidence: 80%
“…These results suggest that T cells have a predesigned program to handle amino acid starvation and that when LAT1 expression is impaired, T cells turn on such a system for restraining the immune response to avoid waste of energy and resources. Interestingly, it has been shown that GCN2 also induces cell cycle arrest by suppressing cycline D3 expression in arginine-starved T cells (39). This and our results suggest that GCN2 functions as a central factor for amino acid starvation response in T cells.…”
Section: Discussionsupporting
confidence: 80%
“…Besides, degradation of L-arginine results in reduced expression of CD3, and consequently impairs T-cell responsiveness. 13,14 Thus, following these theories, L-arginine supplementation was recently proved to enhance T-cell survival and antitumor activity. 15,16 In this study, we tried to validate our hypothesis that L-arginine supplementation and PD-1/PD-L1 pathway blockade can facilitate spontaneous immune response against osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include immune suppressive environments in which tryptophan and arginine are deprived. 20,21 The role of autophagy in these environments is likely to allow T cells to survive in such conditions.…”
Section: Concluding Remarks and Implications For Future Studiesmentioning
confidence: 99%